Rituximab-induced Acute Thrombocytopaenia in a Patient with Mixed Connective Tissue Disease: A Case-based Review - Wahinuddin Sulaiman; Leong Hui Shan (Asian Journal of Medicine & Health Sciences, 2024)
Rituximab-induced acute thrombocytopaenia (RIAT) is a potential adverse drug reaction associated with the use of this therapeutic agent. Majority of the reported cases involved patients with haematological malignancies and its occurrence in autoimmune connective tissue diseases is rare. The pathogenesis of RIAT remains unclear but immune-mediated pathway has been implicated in the mechanism. RIAT runs a benign course and recovery ensues after its onset. Although life-threatening haemorrhage is uncommon, the risk remains significant with severe thrombocytopaenia. Despite being rare, the clinicians should be aware of this phenomenon. Postadministration monitoring of blood counts is pivotal in order to identify its occurrence. This report aims to highlight a case of RIAT with bleeding tendency in a woman with active mixed connective tissue disease.